(untitled) (Journal of Academic Research, 2021)
The judicial ruling is authentic and respected, and it is not permissible to oppose it or disobey it. Because of its sacredness to preserve rights from loss, and that what has previously been presented to the judiciary and has been adjudicated, may not be discussed again with the aim of putting an end to disputes, avoiding contradictory rulings, and taking into account the interests of individuals and groups. For these matters, what is termed "pleading the adjudicated case" or "pleading not accepting the case due to the previous ruling in it" is prescribed in law. The legal jurists differed on the location of the payment of the precedent of the dismissal of the defenses, whether it is from the formal, objective or non-acceptance defenses, provided that the most likely consideration is among the defenses of non-acceptance, and as for its legal ruling it is legitimate with evidence from the Prophet’s Sunnah and the actions of the Companions, may God be pleased with them, and the sayings and actions of the jurists Old-timers. This type of defense is not at all, but it is necessary to fulfill three conditions: the union of the litigants, the union of the subject and the union of the cause, and this defense is part of the general order in Islamic Sharia and the law, so the court decides on its own initiative even if the litigants did not raise it.